2010
DOI: 10.1007/s00330-010-1834-3
|View full text |Cite
|
Sign up to set email alerts
|

Partial “targeted” embolisation of brain arteriovenous malformations

Abstract: The treatment of pial arteriovenous brain malformations is controversial. Little is yet known about their natural history, their pathomechanisms and the efficacy and risks of respective proposed treatments. It is known that only complete occlusion of the AVM can exclude future risk of haemorrhage and that the rates of curative embolisation of AVMs with an acceptable periprocedural risk are around 20 to 50%. As outlined in the present article, however, partial, targeted embolisation also plays a role. In acutel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 31 publications
(37 reference statements)
1
74
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] In AVMs presenting with intracranial hemorrhage, better recognition of certain angioarchitectural features of the AVM as likely weak spots prone to recurrent hemorrhage, such as intranidal-and flow-related aneurysms and venous stenoses, has prompted many operators to perform a partial targeted embolization treatment when complete AVM obliteration is unlikely or impossible. [9][10][11][12][13][14] The growing experience with the use of Onyx in our department together with advancement in imaging possibilities and the adjustment of the technique of curative embolization have gradually resulted in the adaptation of the treatment paradigm of patients with AVMs in our hospital. Embolization is no longer basically restricted to partial nidus obliteration of large AVMs to facilitate subsequent surgery or radiosurgery.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In AVMs presenting with intracranial hemorrhage, better recognition of certain angioarchitectural features of the AVM as likely weak spots prone to recurrent hemorrhage, such as intranidal-and flow-related aneurysms and venous stenoses, has prompted many operators to perform a partial targeted embolization treatment when complete AVM obliteration is unlikely or impossible. [9][10][11][12][13][14] The growing experience with the use of Onyx in our department together with advancement in imaging possibilities and the adjustment of the technique of curative embolization have gradually resulted in the adaptation of the treatment paradigm of patients with AVMs in our hospital. Embolization is no longer basically restricted to partial nidus obliteration of large AVMs to facilitate subsequent surgery or radiosurgery.…”
mentioning
confidence: 99%
“…7,11,12 Others have raised the possibility that seizures are more often related to a disrupted venous outflow pattern than to an inadequacy of arterial blood supply. [13][14][15][16][17] There are only a few studies that have examined the association between individual angioarchitectural characteristics of the BAVM and seizure presentation. 3,18 Turjman et al, 2 in their study of 100 consecutive patients with seizures, and Santos et al, 18 in their study of 170 patients with BAVM, found multiple morphologic features of BAVM associated with seizures.…”
mentioning
confidence: 99%
“…Due to arterialization of the draining vein, drainage of normal brain tissue will be impaired and the amount of tissue impaired by the arterialization will depend on the length of the courseofthedrainingveinsoverunaffectedbrain.Venouscongestion may be accompanied by a cognitive decline or seizures. [13][14][15][16][17]27 From an imaging point of view, the pseudophlebitic pattern (increased tortuosity of pial veins) is a direct reflection of venous congestion. 19 Other signs include delayed venous return of normal brain, venous rerouting, and secondary recruitment of pial superficial veins.…”
mentioning
confidence: 99%
“…[16][17][18][19] Better recognition of certain angioarchitectural features of the AVM as likely weak spots prone to recurrent hemorrhage, such as intranidal-and flow-related aneurysms and venous stenoses, have prompted many operators to perform a partial targeted embolization treatment when complete AVM obliteration is unlikely or impossible. 7,[11][12][13][14][15] Intranidal-and flow-related aneurysms can be excluded from the circulation with Onyx, acrylic glue, or coils, and venous outflow restrictions can be exonerated by occlusion of high-flow intranidal fistula with Onyx under flow arrest with a microballoon. 21 These new developments in the treatment of brain AVMs, in combination with the concurrent and similar advancement of endovascular treatment with Onyx of dural arteriovenous fistulas with drainage to the cortical veins, 22,23 have led our hospital to an adaptation of the diagnosis and treatment strategy in patients with hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Specific elimination of these weak spots or reduction of flow through the AVM by endovascular or surgical therapy is thought to decrease the rate of repeated hemorrhage and to improve prognosis, even when the AVM is only partially obliterated. [11][12][13][14][15][16] With modern endovascular techniques, targeted treatment of AVM-associated aneurysms, partial nidus obliteration with flow reduction, or complete obliteration is possible in most patients with AVMs. [16][17][18][19] In this article, we evaluate the results of a treatment strategy for brain AVMs that present with hemorrhage that includes early angiographic diagnosis and endovascular treatment in the acute phase.…”
mentioning
confidence: 99%